Are Affirmative Action Hires Less Qualified? Evidence from Employer‐Employee Data on New Hires - Holzer, Harry; Neumark, David (Journal of Labor Economics, 1999)
We use microlevel data on employers and employees from a sample of establishments in four major metropolitan areas in the United States to investigate whether Affirmative Action leads to the hiring of minority or female employees who are less qualified. Our measures of qualifications include the educational attainment of the workers hired and a variety of outcome measures related to worker performance on the job. We find evidence of lower educational qualifications among women and minorities hired under Affirmative Action. However, we do not find evidence of weaker job performance among most groups of minority and female Affirmative Action hires.